If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -8(r + 7) = -93 Reorder the terms: 3 + -8(7 + r) = -93 3 + (7 * -8 + r * -8) = -93 3 + (-56 + -8r) = -93 Combine like terms: 3 + -56 = -53 -53 + -8r = -93 Solving -53 + -8r = -93 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '53' to each side of the equation. -53 + 53 + -8r = -93 + 53 Combine like terms: -53 + 53 = 0 0 + -8r = -93 + 53 -8r = -93 + 53 Combine like terms: -93 + 53 = -40 -8r = -40 Divide each side by '-8'. r = 5 Simplifying r = 5
| 15-7b+3b=35 | | 19m+-17m=-18 | | 0.7p+4.6=7.3-0.2p | | log(w+9)-log(w-4)=1 | | 17z-14z-z+5=-13 | | 2.5(w-4)=5 | | 3x-4+3=4 | | 5n^3-25n^2=0 | | -0.75*x=12 | | x-1+6x=-1 | | 9(d-4)-8=5d | | 224=(W-8)-W-(W-8)-W | | 2r-3.2=1.7 | | 8=5x-2(x+5) | | 7x-3=-6x+75 | | 47-3n=-23 | | Q-q+q+q=18 | | 5x=-3x-32 | | -3(r-6)=-9 | | 8x+4y=188 | | 6(x-9)-4(x+8)=1 | | 5log(x-5)=12 | | -4m+6=-8 | | -13n-(-2n)-(-15n)+-17n-(-10n)-10=5 | | 2y+4=y+7 | | 3x+3(1-x)=-17 | | 3x-2=5x-2 | | 84=6(m+7) | | (2x-1)+3(3x-5)=-2(2x+1) | | 10y+7=17 | | -x=-2x-1 | | 4q-3q+2q-1=11 |